Influence of immunosuppression in patients with severe acute respiratory distress syndrome on veno‐venous extracorporeal membrane oxygenation therapy. Issue 9 (4th May 2021) - Rilinger, Jonathan; Zotzmann, Viviane; Bemtgen, Xavier; Rieg, Siegbert; Biever, Paul M.; Duerschmied, Daniel; Pottgiesser, Torben; Kaier, Klaus; Bode, Christoph; Staudacher, Dawid L.; Wengenmayer, Tobias
Abstract: Prognosis of patients suffering from acute respiratory distress syndrome (ARDS) is poor. This is especially true for immunosuppressed patients. It is controverisal whether these patients should receive veno‐venous extracorporeal membrane oxygenation (VV ECMO) while evidence on this topic is sparse. We report retrospective data of a single‐center registry of patients with severe ARDS requiring ECMO support between October 2010 and June 2019. Patients were analyzed by their status of immunosuppression. ECMO weaning success and hospital survival were analyzed before and after propensity score matching (PSM). Moreover, ventilator free days (VFD) were compared. A total of 288 patients were analyzed (age 55 years, 67% male), 88 (31%) presented with immunosuppression. Survival rates were lower in immunosuppressed patients (27% vs. 53%, P < .001 and 27% vs. 48% after PSM, P = .006). VFD (60 days) were lower for patients with immunosuppression (11.9 vs. 22.4, P < .001), and immunosuppression was an independent predictor for mortality in multivariate analysis. Hospital survival was 20%, 14%, 35%, and 46% for patients with oncological malignancies, solid organ transplantation, autoimmune diseases, and HIV, respectively. In this analysis immunosuppression was an independent predictor for mortality. However, there were major differences in the weaning and survival rates between the etiologies of immunosuppression which should be considered in decision making. Abstract : Hospital survival of patients with extracorporeal membrane oxygenation support and immunosuppression. Hospital survival rate of immunosuppressed patients was lower than in immunocompetent patients ( P < .001). Moreover, there were major differences in the survival rates between the etiologies of immunosuppression. Patients with immunosuppression in case of oncological disease or after solid organ transplantation showed significantly reduced survival compared to patients without immunosuppression ( P < .001 and P = .047). Patients with autoimmune disease had numerically but not significantly reduced survival rates ( P = .070). Survival of immunosuppressed HIV patients was similar to patients without immunosuppression ( P = .761).